Penerapan E-Bupot PPh 23 Unifikasi dalam Sistem Coretax Sebagai Transformasi Digital Perpajakan Indonesia Pada PT ABC (Jurnal Riset Manajemen dan Akuntansi, 2025)
The digital transformation of taxation in Indonesia is an effort by the Directorate General of Taxes to enhance the efficiency and effectiveness of the national tax system. This study aims to analyze the implementation of E-Bupot PPh 23 Unification within the CoreTax system at PT ABC as part of Indonesia's digital tax transformation. The research method used is descriptive qualitative through observation and documentation of the use of E-Bupot PPh 23 unification. The research results indicate that the integration of E-Bupot PPh 23 Unification into the CoreTax system has improved operational efficiency through the automation of tax calculations by 2% of the gross amount for services and the unification of the processes of creating withholding tax certificates, deposits, and SPT reporting into one platform. Although challenges were found in user adaptation and integration with existing infrastructure, this digital transformation has streamlined the tax administration process at PT ABC and reflects progress in tax reform in Indonesia.